Eco-Innovation Research in Indonesia: A Systematic Review and Future Directions - Budi Harsanto (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2020)
Innovation by considering the impact to the ecological environment, known as eco-innovation, continues to receive increasing attention in at least the past two decades. This paper aims to provide an analysis on recent development of eco-innovation research in Indonesia and provide some potential avenues for future research. Analysis is carried out using systematic literature review (SLR) techniques to synthesize knowledge development of a scientific field in a structured, transparent, and reliable manner. The search was conducted on three academic databases, including Scopus, Google Scholar, and the local academic database of Garuda (Garba Rujukan Digital). Data analyzed using content analysis. The analysis shows that scholarly publication of eco-innovation research in Indonesia is still rare. The topics discussed can be categorized into several categories such as the driver of eco-innovation, R&D for eco-innvation, eco-innovation performance, which addresses various types of eco-innovation and different level of analysis. Potential research avenues are then identified at the end of the paper. This is the first systematic review on eco-Innovation in Indonesia, and first combining systematic search strategy in the both local and international academic database.